Essence & Significance of Work Culture for Organisations in Indian Context – A Case Approach - Sweta Singh; Lina Prajapati; Dr. Rajesh Kumar Pandey (International Journal of Engineering and Management Research, 2024)
Culture signifies the way that a domain is managed. Be it an Organisation or be it personal character, all need to manage their respective Culture. The Work Culture at Organisations need to be managed essentially to get better productivity. Workplace culture is the collective personality of an organization, shaping the work environment and influencing employee interactions with tasks, colleagues, and clients. A positive culture fosters employee engagement, boosting productivity and creativity. This attempt in the form of a case approach is an exploratory study conducted with the help of massively secondary data and Primary Data in the form of Interview Method. The Authors have Interviewed Industry Representatives to collect the view points on the theme of the study and cited a Case of E Sreedharan as Insight from the Study. The Authors aim to study the Essence & Significance of Work Culture at Organizations. The Authors further aim to interpret the professional life experiences of E. Sreedharan, the Metro Man of India through selected projects undertaken by him that depicts the work culture across organisations. The study further aims to contribute a recommendary Model for Development of Work Culture at Organisations. Also the study has the potential to be a literature for further studies in this regard. The Authors have considered the Work Culture at Organisations at large rather any specific sector or any specific region for study. The Theme of the study may have various other elements associated. Hence this may be a limitation of the study as the inferences are indicative in nature rather exhaustive.